SCREENING OF THE SAMPLES OF SUDAN GRASS VARIETIES IN THE SARATOV REGION - S. S. Kukoleva; D. S. Semin; O. P. Kibalnik; V. I. Starchak (Зерновое хозяйство России, 2018)
The article presents the study results of the collection ofSudangrass on green chop and dry matter productivity. The purpose of the study is a clustering and determining of the samples ofSudangrass varieties according to the main economic traits for the further use in the selection on heterosis. To optimize the breeding process there has been used a clustering analysis which allows grouping a large amount of variety samples into several groups (classes) with differ in some parameters. The samples ofSudangrass varieties have been grown in the trials of FSBSI RusRIA “Rossorgo” in the years of 2015-2015. The area of the plot was7.7 m2. It was a three crop rotation sequence. The density of plant stand was 1.0 ml/ha. The study showed that the middle maturing samples form the best productivity of green chop and dry matter. During two cuttings the samples ‘Allegoriya’, ‘Anastasiya’ and ‘Aleksandrina’ gave 59.2-63.0 t/ha and 8.8-15.07 t/ha of green chop and dry matter respectively. The variance analysis (unorganized sequences) confirms the correctness of the sample distribution in clusters. According to all studied traits the differences of clusters are credible, excluding the trait ‘general tillering’. The use of various methods of the statistics gave the opportunity to group the samples of Sudangrass varieties into 8 clusters according to their main economically valuable traits. The largest number of differences (45) has been determined for the cluster 7. The least number has been found in the clusters 1 and 4. The variety samples of the first and second cuttings have been determined as the samples with the best productivity of green chop and dry matter.